Type: Article
Publication Date: 1988-01-01
Citations: 17
DOI: https://doi.org/10.1090/s0002-9939-1988-0946624-9
We give a comparison theorem for eigenvalues for a <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="left-parenthesis k comma n minus k right-parenthesis"> <mml:semantics> <mml:mrow> <mml:mo stretchy="false">(</mml:mo> <mml:mi>k</mml:mi> <mml:mo>,</mml:mo> <mml:mi>n</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mi>k</mml:mi> <mml:mo stretchy="false">)</mml:mo> </mml:mrow> <mml:annotation encoding="application/x-tex">(k,n - k)</mml:annotation> </mml:semantics> </mml:math> </inline-formula>-conjugate boundary value problem for the systems <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="left-parenthesis negative 1 right-parenthesis Superscript n minus k Baseline upper L y equals lamda upper P left-parenthesis t right-parenthesis y"> <mml:semantics> <mml:mrow> <mml:mrow class="MJX-TeXAtom-ORD"> <mml:mo stretchy="false">(</mml:mo> <mml:mo>β<!-- β --></mml:mo> <mml:mn>1</mml:mn> <mml:msup> <mml:mo stretchy="false">)</mml:mo> <mml:mrow class="MJX-TeXAtom-ORD"> <mml:mi>n</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mi>k</mml:mi> </mml:mrow> </mml:msup> </mml:mrow> <mml:mi>L</mml:mi> <mml:mi>y</mml:mi> <mml:mo>=</mml:mo> <mml:mi>Ξ»<!-- Ξ» --></mml:mi> <mml:mi>P</mml:mi> <mml:mo stretchy="false">(</mml:mo> <mml:mi>t</mml:mi> <mml:mo stretchy="false">)</mml:mo> <mml:mi>y</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">{( - 1)^{n - k}}Ly = \lambda P(t)y</mml:annotation> </mml:semantics> </mml:math> </inline-formula> and <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="left-parenthesis negative 1 right-parenthesis Superscript n minus k Baseline upper L z equals normal upper Lamda upper Q left-parenthesis t right-parenthesis z"> <mml:semantics> <mml:mrow> <mml:mrow class="MJX-TeXAtom-ORD"> <mml:mo stretchy="false">(</mml:mo> <mml:mo>β<!-- β --></mml:mo> <mml:mn>1</mml:mn> <mml:msup> <mml:mo stretchy="false">)</mml:mo> <mml:mrow class="MJX-TeXAtom-ORD"> <mml:mi>n</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mi>k</mml:mi> </mml:mrow> </mml:msup> </mml:mrow> <mml:mi>L</mml:mi> <mml:mi>z</mml:mi> <mml:mo>=</mml:mo> <mml:mi mathvariant="normal">Ξ<!-- Ξ --></mml:mi> <mml:mi>Q</mml:mi> <mml:mo stretchy="false">(</mml:mo> <mml:mi>t</mml:mi> <mml:mo stretchy="false">)</mml:mo> <mml:mi>z</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">{( - 1)^{n - k}}Lz = \Lambda Q(t)z</mml:annotation> </mml:semantics> </mml:math> </inline-formula>, where <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper P left-parenthesis t right-parenthesis"> <mml:semantics> <mml:mrow> <mml:mi>P</mml:mi> <mml:mo stretchy="false">(</mml:mo> <mml:mi>t</mml:mi> <mml:mo stretchy="false">)</mml:mo> </mml:mrow> <mml:annotation encoding="application/x-tex">P(t)</mml:annotation> </mml:semantics> </mml:math> </inline-formula> and <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper Q left-parenthesis t right-parenthesis"> <mml:semantics> <mml:mrow> <mml:mi>Q</mml:mi> <mml:mo stretchy="false">(</mml:mo> <mml:mi>t</mml:mi> <mml:mo stretchy="false">)</mml:mo> </mml:mrow> <mml:annotation encoding="application/x-tex">Q(t)</mml:annotation> </mml:semantics> </mml:math> </inline-formula> are continuous <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="m times m"> <mml:semantics> <mml:mrow> <mml:mi>m</mml:mi> <mml:mo>Γ<!-- Γ --></mml:mo> <mml:mi>m</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">m \times m</mml:annotation> </mml:semantics> </mml:math> </inline-formula> matrix functions. We assume that the corresponding scalar equation <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper L x equals 0"> <mml:semantics> <mml:mrow> <mml:mi>L</mml:mi> <mml:mi>x</mml:mi> <mml:mo>=</mml:mo> <mml:mn>0</mml:mn> </mml:mrow> <mml:annotation encoding="application/x-tex">Lx = 0</mml:annotation> </mml:semantics> </mml:math> </inline-formula> is <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="left-parenthesis j comma n minus j right-parenthesis"> <mml:semantics> <mml:mrow> <mml:mo stretchy="false">(</mml:mo> <mml:mi>j</mml:mi> <mml:mo>,</mml:mo> <mml:mi>n</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mi>j</mml:mi> <mml:mo stretchy="false">)</mml:mo> </mml:mrow> <mml:annotation encoding="application/x-tex">(j,n - j)</mml:annotation> </mml:semantics> </mml:math> </inline-formula>-disconjugate for <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="k minus 1 less-than-or-equal-to j less-than-or-equal-to n minus 1"> <mml:semantics> <mml:mrow> <mml:mi>k</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mn>1</mml:mn> <mml:mo>β€<!-- β€ --></mml:mo> <mml:mi>j</mml:mi> <mml:mo>β€<!-- β€ --></mml:mo> <mml:mi>n</mml:mi> <mml:mo>β<!-- β --></mml:mo> <mml:mn>1</mml:mn> </mml:mrow> <mml:annotation encoding="application/x-tex">k - 1 \leq j \leq n - 1</mml:annotation> </mml:semantics> </mml:math> </inline-formula>. A special case of this is when <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper L x equals 0"> <mml:semantics> <mml:mrow> <mml:mi>L</mml:mi> <mml:mi>x</mml:mi> <mml:mo>=</mml:mo> <mml:mn>0</mml:mn> </mml:mrow> <mml:annotation encoding="application/x-tex">Lx = 0</mml:annotation> </mml:semantics> </mml:math> </inline-formula> is disconjugate; our results are new even in this case.